Dry matter and organic matter wafer feed and level Trembesi leaves (S. saman). (March 2019) - Islamiyati, R; Ismartoyo,; Mide, M Z
Abstract: The main problem in the development of ruminant livestock production is the availability of feed on a continuous basis both in quality and quantity. An efficient feeding strategy is utilizing abundant and nutritious local resources for livestock. Waste agricultural and plantation crops such as corn cobs have a lower quality and palatability. Wafer is an offered alternative solution, by adding trembesi leaves that tree legume and available throughout the year. The experimental design used a completely randomized design (CRD) with 5 treatments and 4 replications. Trembesi leaves was on level (0%, 5%, 10%, 15%, 20%) in feed wafers. Parameters observed was dry matter and organic matter on feed wafer stored for four weeks. Analytical statistic showed significantly effect (P <0.05) on organic matter and no significant effect (P> 0.05) on dry matters content. It could be concluded that the level of trembesi leaves in wafer feed increased on dry matter dan organic matter.